Hildenbrandia (Hildenbrandiales, Florideophyceae) from Japan and taxonomic lumping of H. jigongshanensis and H. japananensis. Issue 3 (17th February 2021) - Vieira, Christophe; Akita, Shingo; Uwai, Shinya; Hanyuda, Takeaki; Shimada, Satoshi; Kawai, Hiroshi
SUMMARY: The genetic diversity of freshwater Hildenbrandia species (Florideophyceae, Hildenbrandiales) from Japan was reassessed based on specimens collected from Kagoshima (Kyushu), Hyogo and Kanagawa Prefectures (Honshu), using rbc L and 18S rDNA sequences. Phylogenetic results suggested the occurrence of only one species of freshwater Hildenbrandia in Japan, H. japananensis . The clade H. jigongshanensis – H. japananensis is sister to H. rivularis . Hildenbrandia angolensis was paraphyletic and positioned basally among the freshwater Hildenbrandia clades. Furthermore, the genetic similarity between H. jigongshanensis and H. japananensis determined by rbc L and 18S sequences as well as the intraspecific morphological plasticity led us to the conclusion that the species from China and Japan were conspecific. Accordingly, we propose the taxonomic lumping of H. jigongshanensis and H. japananensis . In addition, we recommend additional molecular and morphological studies on Asian freshwater Hildenbrandia to determine whether H. jigongshanensis is conspecific with H. ramanaginae previously described from India.